Viral zoonoses assessment in invasive rodent species from São Tomé and Príncipe - Tereza Almeida; Maria Carolina Matos; Daniel A. Velarde-Garcéz; Vanessa A. Mata; Marquinha Martins; Conceição Neves; Pedro Beja; Ana M. Lopes; Joana Abrantes (PLoS ONE, 2026)
Zoonoses are diseases transmitted from animals to humans, highlighting the inseparable link between animal and human health. They are responsible for approximately 2.4 billion cases of illness and 2.2 million deaths annually, posing a significant challenge to public health and food security. Transmission of infectious agents from animals to humans occurs through direct contact, ingestion, inhalation, or inoculation of the infectious agent. Finding practical ways to monitor the presence and/or abundance of zoonotic pathogens is important to estimate the risk of spillover to humans. Since rodents are present almost everywhere, live in proximity with humans and host several zoonotic viruses, we conducted a screening in different tissue samples of black rats ( Rattus rattus ) and brown rats ( Rattus norvegicus) collected in São Tomé and Príncipe in 2021 and 2022 for the presence of five zoonotic families of viruses, including Arenaviridae , Coronaviridae , Flaviviridae , Hantaviridae , and Poxviridae . Although we found no evidence of the presence of these viral taxa among the rodent samples tested, our study does not exclude their presence in São Tomé and Príncipe. Continued monitoring of these and other zoonotic viruses is advisable to prevent or mitigate the emergence of viral diseases that are often fatal to humans.